Recent advances in the applications and biotechnological production of mannitol. (September 2017) - Dai, Yiwei; Meng, Qing; Mu, Wanmeng; Zhang, Tao
Highlights: Attention on mannitol production by fermentation is received in recent years. Fermentation factors affected the mannitol yield are listed. Mannitol applications in food, pharmaceutical and chemical industries are reviewed. Abstract: Mannitol is a polyol or an alditol that is naturally found in many plants and can be produced by several microorganisms. Based on its beneficial physiological effects, mannitol is currently used as a functional sweetener in the food industry. In addition, mannitol has applications in pharmaceutical, chemical and medical industries because of its promising advantages. Mannitol can be produced by extraction, chemical synthesis, or fermentation. Certain mutants have been constructed for different purposes. In this review, we focused on recent advances in the applications and biotechnological production of mannitol.